Potential use of the Black Soldier Fly (BSF) in Poultry Production - Penido , Wanderson Duarte; Souza , Thamírys Vianelli Maurício de; Vasconcellos , Carlos Henrique Figueiredo; Souza , Matheus Faria de; Siqueira , Bruna Pereira; Stringhini , José Henrique (Seven Editora, 2023)
The aim of this article is to encourage debate and sharing of studies and research on the use of Black Soldier Fly (BSF) in poultry feed. It is observed that in Brazilian poultry, feeds are mainly based on cereals, which must be supplemented with high quality animal protein and essential amino acids. Among the alternative ingredients for monogastric diets, the use of insects has stood out and among the insects used, black soldier fly flour or BSF (Hermetia illucens) is an attractive candidate, as it contains excellent nutritional characteristics and high production of biomass, in addition to its ability to promote the degradation of a series of materials of organic origin,  converting them into an important source for animal feed. It is concluded that, although promising as a food component in the diet of poultry, the current cost to produce these insects in the country is still high and a relevant factor when compared to sources such as fish meal and soybean meal. Other challenges, such as the standardization of the bromatological compositions of flours derived from these insects, increased production, as well as a cultural change in the Western way of seeing these organisms, are issues to be addressed. DOI:https://doi.org/10.56238/alookdevelopv1-194